Comparative cross-linking and mass spectrometry of an intact F-type ATPase suggest a role for phosphorylation - Schmidt, C; Zhou, M; Marriott, H; Morgner, N; Politis, A; Robinson, C (Springer Nature, 2013)
F-type ATPases are highly conserved enzymes used primarily for the synthesis of ATP. Here we apply mass spectrometry to the F1FO-ATPase, isolated from spinach chloroplasts, and uncover multiple modifications in soluble and membrane subunits. Mass spectra of the intact ATPase define a stable lipid ‘plug’ in the FO complex and reveal the stoichiometry of nucleotide binding in the F1 head. Comparing complexes formed in solution from an untreated ATPase with one incubated with a phosphatase reveals that the dephosphorylated enzyme has reduced nucleotide occupancy and decreased stability. By contrasting chemical cross-linking of untreated and dephosphorylated forms we show that cross-links are retained between the head and base, but are significantly reduced in the head, stators and stalk. Conformational changes at the catalytic interface, evidenced by changes in cross-linking, provide a rationale for reduced nucleotide occupancy and highlight a role for phosphorylation in regulating nucleotide binding and stability of the chloroplast ATPase.